Strengthening Religious Moderation through the Merdeka Curriculum: The Role of Islamic Religious Education Teachers at Public Senior High School - Haris, Abdul; Mardani, Dede Aji; Kusnandar, Endang; Mas'ad, Muhammad Aunurrochim (Badan Litbang dan Diklat Kementerian Agama RI, 2024)
Religious moderation as a perspective can be a solution for opening up to each other, accepting differences, and maintaining harmony between religious communities. Strengthening moderation should also be introduced to students from an early age so that they are not easily influenced by radical religious thoughts. Through education and implementation of the values of religious moderation, it is hoped that religious conflict and extremism can be reduced and strengthening tolerance between religious communities. This effort is also reflected in changes to the education curriculum which integrates the values of religious moderation to create a peaceful and inclusive learning environment. Therefore, researchers want to see the role of Islamic Religious Education Teachers in Implementing Religious Moderation in the Context of the Merdeka curriculum at SMAN 1 Tasikmalaya City. This research aims to: 1) To determine the implementation of religious moderation in the Merdeka curriculum at SMAN 1 Tasikmalaya City. 2) To find out the role of PAI teachers in implementing and improving religious moderation in the Merdeka curriculum at SMAN 1 Tasikmalaya City. 3) To find out what are the supporting and inhibiting factors for PAI teachers in increasing religious moderation in the Merdeka curriculum at SMAN 1 Tasikmalaya City. The type of research used is descriptive qualitative research with data collection techniques using observation, interviews and documentation methods. The analysis techniques used are data reduction, data presentation, and drawing conclusions. The research results show that: 1) the role of teachers is not only as teaching staff, but also as demonstrators, class managers, motivators and evaluators. 2) forms of religious moderation activities in the Merdeka curriculum at SMAN 1 Tasikmalaya City, namely: a) holding extracurricular activities and competitions as a form of preventing violence b) carrying out social services and religious studies, and holding competitions to foster an attitude of tolerance c) carrying out activities in the month Ramadan, birthdays, birthdays, commemorating teachers' day, implementing the 3S culture as a form of accommodating local culture. 3) Supporting factors in increasing religious moderation in the Merdeka curriculum at SMAN 1 Kota Tasikmalaya. There is support from the school principal, that the principal really supports all religious policies at SMAN 1 Kota Tasikmalaya as long as they do not conflict with the teachings of their respective religions and of course also do not conflict. with the educational goals and vision and mission of the school. 4) obstacles in instilling the values of religious moderation at SMAN 1 Tasikmalaya City, namely: a) students have different characters, b) lack of upbringing in the family c) bringing bad habits from home.